P-106 Embedding palliative care in the ED. (20th March 2022) - Hall, Hannah; Frew, Katie; Armstrong, Leonie; Spriggs, Helena; Atkinson, Kate
Abstract : Background: Acute hospital admission of people with palliative care needs is of ongoing concern, in a time of significant pressure for NHS services as a whole, and emergency departments (ED) in particular. This population may have recurrent and frequent healthcare needs, and when requiring inpatient care will most often be admitted via the ED. This makes the ED an important site for specialist palliative care assessment. Method: From November 2020 a designated Clinical Nurse Specialist (CNS) from the Specialist Palliative Care Team (SPCT) collaborated with ED clinicians and mangers to provide a 5-day service working proactively into the ED while also delivering an 'on-the-floor' teaching package. Prospective data regarding the patient outcomes were collected over the course of one year (to November 2021) and compared to data from the SPCT database from the previous year. A retrospective evaluation of the impact of the education package was conducted. Results: In 2019/20 5 patients were seen by the SPCT in the ED: in 2020/21 this had risen to 168. 38 patients were discharged home for end-of-life-care from the ED: 37 were transferred to a Palliative Care Unit (PCU) from the ED and 91 were admitted to other wards within the hospital. 2 patients died in the ED with support from the SPCT. 30 clinicians participated in the training, and demonstrated an increase in confidence scores in 3 key domains: setting up a syringe driver, discharge from the ED and prescribing of anticipatory medication in the ED. Conclusion: Targeted palliative care input within the ED can support patients with symptom control and to be in their preferred place of care. An 'on-the-floor' education package can be successfully delivered even in a pandemic. Specific skills are required from SPCTs in this hyper-acute environment.